Exploring Political Views on Synthetic Biology in the Netherlands - Rerimassie, Virgil (Nanoethics, 2016)
Synthetic biology may be an important source of progress as well as societal and political conflict. Against this backdrop, several technology assessment organizations have been seeking to contribute to timely societal and political opinion-making on synthetic biology. The Rathenau Instituut, based in the Netherlands, is one of these organizations. In 2011, the institute organized a ‘Meeting of Young Minds’: a young people’s debate between ‘future synthetic biologists’ and ‘future politicians’. The former were represented by participants in the international Genetically Engineered Machines competition (iGEM), the latter by political youth organizations (PYOs) linked to Dutch political parties. The Rathenau Instituut found seven PYOs—including right wing, left wing, Green and Christian groups—willing to commit to an intensive process aimed at formulating a tentative partisan view on synthetic biology and discussing it with fellow PYOs and iGEM participants. Given the minimal amount of available data on how political parties understand synthetic biology, mapping the debate may provide valuable insights. In this article, I aim to provide such a mapping exercise and also to reflect on how and why the Rathenau Instituut organized the event.